Analysis of risk factors related to thyroid function abnormality caused by programmed death-1 inhibitors - Lihong WANG; Huiyang SONG; Shufei ZANG; ling YE; Xuefei DANG (Zhongguo Linchuang Yixue)
ObjectiveTo investigate the clinical characteristics and influencing factors of thyroid function abnormality (TFA) in patients with malignant tumors receiving programmed death-1 (PD-1) inhibitor therapy, and its correlation with PD-1 inhibitors. MethodsA retrospective analysis was conducted on the clinical data and biochemical indicators of 669 patients with malignant tumors who received PD-1 inhibitor therapy. Of these, 561 patients maintained normal thyroid function (normal group), while 108 developed TFA (TFA group). Baseline characteristics, PD-1 inhibitor type, tumor type, and other indice were compared between the two groups. Univariate and multivariate logistic regression analyses were performed to identify related factors for TFA development. Additionally, the relationship between PD-1 inhibitors and TFA types was further analyzed within the TFA group.ResultsThe rates of patients treated with pembrolizumab and with respiratory tumors were significantly higher in TFA group than those in the normal group (P＜0.01). Multivariate logistic regression analysis revealed that treatment with pembrolizumab and with respiratory tumor increased 5.350 and 1.514 times than tislelizumab and digestive tumor for risk of TFA development, respectively (P＜0.01). Within the TFA group, hypothyroidism was the predominant type (75, 69.4%); treatment with pembrolizumab increased 2.999 times than tislelizumab for development risk of hyperthyroidism (P＝0.042). ConclusionsAmong patients with malignant tumors treated with PD-1 inhibitors, pembrolizumab is more frequently associated with TFA, and patients with respiratory tumors were at a higher risk of developing TFA. Clinicians should closely monitor thyroid function in patients with respiratory tumors treated with pembrolizumab.